Macro-Economic and Product Challenges Facing Vietnamese the Pangasius Industry. Issue 2 (3rd April 2018) - Nguyen, Tram Anh Thi; Jolly, Curtis M.
ABSTRACT: Vietnamese pangasius achieved global status as a highly competitive whitefish as exports to Europe, United States, Asian, and Latin American countries have grown at a rapid pace. Accelerated growth rates have met with a number of challenges that can be potentially converted to opportunities to foster further progress and expansion in exports. This study is a review of literature that examines the various economic and market issues facing the industry in the EU market. The review suggests that at the domestic level farmers must be organized alongside vertical integration to improve quality and supply consistency. Vertical integration may help reduce farm operating costs and increase farmer profit. High interest rates, fluctuating exchange rates, access to credit, lack of capital acquisition by small farmers, and product risks are key economic issues confronting the industry, whereas product quality and standards, product image, and rejection pose financial pressure on farmers, processors, and exporters. The fish, pangasius competes well in the white fish market and key product characteristics are well suited to vertical integration and horizontal differentiation in various and diverse EU markets. The industry may employ a combination of vertical and mixed product differentiation for improved product image and market share expansion in the EU white fish market.